2020
DOI: 10.1177/0021998320964553
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mechanical properties of hydroxyapatite composites reinforced with i-Al64Cu23Fe13 quasicrystal

Abstract: Mechanical behavior of hydroxyapatite-based composites (HAp) was studied as a function of the reinforcement concentration of the quasicrystalline (QC) Al64Cu23Fe13 alloy. The synthesis of the HAp matrix was carried out by sol-gel method, while the synthesis of the QC was performed by an arc furnace with a subsequent thermal treatment. The composites were made by powder metallurgy and cold compacted to form test pieces that were sintered with a constant flow of argon. The materials were characterized using X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Silver ions integrated into HA particles can be reduced by γ-irradiation to create Ag nanoparticle/HA biocomposites [670]. More complicated formulations, such as Ag/Ag 3 PO 4 /BCP (HA + β-TCP) [1035], Ti6Al4V/HA/TiB 2 [1030], HA/i-Al 64 Cu 23 Fe 13 quasicrystals [1029], and CaSiO 3 /HA reinforced with a Ti6Al4V alloy [1039], were prepared as well.…”
Section: Biocomposites With Glasses Inorganic Compounds Metals and Ca...mentioning
confidence: 99%
“…Silver ions integrated into HA particles can be reduced by γ-irradiation to create Ag nanoparticle/HA biocomposites [670]. More complicated formulations, such as Ag/Ag 3 PO 4 /BCP (HA + β-TCP) [1035], Ti6Al4V/HA/TiB 2 [1030], HA/i-Al 64 Cu 23 Fe 13 quasicrystals [1029], and CaSiO 3 /HA reinforced with a Ti6Al4V alloy [1039], were prepared as well.…”
Section: Biocomposites With Glasses Inorganic Compounds Metals and Ca...mentioning
confidence: 99%
“…The quasicrystalline icosahedral ψ-phase in the Al-Cu-Fe system is known to be stable under the temperature of ∼800°C [10][11][12] which is higher than the operating temperature of Al-based alloys. Thus, a magnetron sputtering [16], electron beam (EB) PVD technique [17,18], or plasma spraying [19][20][21][22][23][24] were used to produce the QC coatings. It was shown that their hardness and wear resistance values are comparable to or even higher than that of the natural composites containing QC particles distributed in the bcc β-phase [25][26][27][28][29], multi-phase alloys, or artificial Al-based composite layers containing QC particles [30][31][32].…”
Section: Introductionmentioning
confidence: 99%